Experimental study of fracture plugging effectiveness for improving the fracture pressure of a low bearing capacity formation. (4th March 2022) - Rwechungula, James Cleophace; Cheng, Yuanfang; Han, Zhongying
Abstract: Wellbore strengthening by fracture plugging is an effective method for controlling fluid leakage in a fractured formation. However, few experiments have documented the effectiveness of fracture plugging on formation leakage. In this study, fracture plugging of fractured carbonate formation was conducted using a novel plugging dynamic core device. The samples were processed into standard cores before creating fractures. Fracture plugging was assessed using the fracture pressure bearing capacity, whose higher values indicate better plugging effectiveness. A generalized linear model (GLM) has been proposed to correlate the effects of confining pressure, fracture porosity, and plugging agent content (PAC) on the fracture pressure bearing capacity. According to this model, the fracture porosity has a greater effect on the fracture pressure than the confining pressure and plugging content. The model also revealed that as the fracture porosity increased by 10%, the fracture pressure bearing capacity decreased by 10.3%, while an increase in the confining pressure by the same magnitude resulted in a 5.3% increase in the fracture pressure. The experimental results were successfully verified in the field by applying a 30% plugging agent in two wells. An improvement in the fracture pressure bearing capacity in two vulnerable sections of the wells was observed.